Molecular and genetic organization of bands and interbands in the dot chromosome of Drosophila melanogaster - Sidorenko, Darya S. (Chromosoma, 2019)
The fourth chromosome smallest in the genome of Drosophila melanogaster differs from other chromosomes in many ways. It has high repeat density in conditions of a large number of active genes. Gray bands represent a significant part of this polytene chromosome. Specific proteins including HP1a, POF, and dSETDB1 establish the epigenetic state of this unique chromatin domain. In order to compare maps of localization of genes, bands, and chromatin types of the fourth chromosome, we performed FISH analysis of 38 probes chosen according to the model of four chromatin types. It allowed clarifying the dot chromosome cytological map consisting of 16 loose gray bands, 11 dense black bands, and 26 interbands. We described the relation between chromatin states and bands. Open aquamarine chromatin mostly corresponds to interbands and it contains 5′UTRs of housekeeping genes. Their coding parts are embedded in gray bands substantially composed of lazurite chromatin of intermediate compaction. Polygenic black bands contain most of dense ruby chromatin, and also some malachite and lazurite. Having an accurate map of the fourth chromosome bands and its correspondence to physical map, we found that DNase I hypersensitivity sites, ORC2 protein, and P–elements are mainly located in open aquamarine chromatin, while element 1360, characteristic of the fourth chromosome, occupies band chromatin types. POF and HP1a proteins providing special organization of this chromosome are mostly located in aquamarine and lazurite chromatin. In general, band organization of the fourth chromosome shares the features of the whole Drosophila genome. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00412-019-00703-x) contains supplementary material, which is available to authorized users.